2021
DOI: 10.1093/gerona/glab096
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pulmonary Function With Cognitive Decline in Older Adults: A Nationwide Longitudinal Study in China

Abstract: This study aimed to examine whether pulmonary function and cognition are independently associated at multiple time points. We included 8264 participants (49.9% women) aged 50-94 years at baseline from the China Health and Retirement Longitudinal Study in our analysis. Participants were enrolled in 2011 and followed up in 2013 and 2015. Cognitive function was assessed through a face-to-face interview in each survey. Pulmonary function was assessed via peak expiratory flow. Pulmonary function and cognitive funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
2
6
2
Order By: Relevance
“…Although the underlying mechanisms are unclear, our study is supported by recent evidence that poor pulmonary function might accelerate cognitive decline. 10 , 11 Our study is consistent with a previous study demonstrating that digestive disorders (diverticulitis and dyspepsia) were associated with a higher risk of dementia. 13 Inflammation in those with digestive disorders might increase the risk of dementia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although the underlying mechanisms are unclear, our study is supported by recent evidence that poor pulmonary function might accelerate cognitive decline. 10 , 11 Our study is consistent with a previous study demonstrating that digestive disorders (diverticulitis and dyspepsia) were associated with a higher risk of dementia. 13 Inflammation in those with digestive disorders might increase the risk of dementia.…”
Section: Discussionsupporting
confidence: 92%
“… 8 Little is known regarding the association between types of cancers and incident dementia. It is also of great importance to confirm the associations of emerging risk factors for dementia including musculoskeletal disorders, painful conditions, 9 respiratory disorders (such as chronic obstructive pulmonary disease [COPD]), 10 , 11 chronic kidney disease (CKD), 12 and digestive disorders 13 with dementia in large prospective cohort studies. A recent prospective study has identified several physical diseases including erysipelas, hypothyroidism, duodenal ulcer, gastritis, and duodenitis (in addition to conventional risk factors), that may increase the long-term risk of dementia.…”
Section: Introductionmentioning
confidence: 99%
“…A longitudinal study of older Chinese adults demonstrated that the positive association between pulmonary function and cognition was stronger in females ( 17 ). Similar to our results, participants with poor pulmonary function had higher odds of MCI in the female group and in the physically inactive group.…”
Section: Discussionmentioning
confidence: 99%
“…Data retrieved from the AGES-Reykjavik Study revealed that lower pulmonary function measured in midlife predicted poor memory, processing speed, executive function, MCI and dementia 23 years later ( 12 ). Accumulating epidemiological studies have also illustrated that the global cognitive decline and a greater risk of dementia have a significant relationship to indicators with pulmonary function expressed as forced vital capacity (FVC), forced expiratory volume in 1 second (FEV1) and peak expiratory flow (PEF) ( 12 17 ). However, previous studies have either focused on the association of COPD with dementia or MCI, or have targeted community-dwelling participants with relatively higher education and socioeconomic backgrounds, whereas information about the relationship between pulmonary function and MCI in rural populations is scarce ( 14 17 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation